2020
DOI: 10.1080/14786419.2020.1793150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vivo safety of tucumã oil nanocapsules in an experimental model of silver catfish Rhamdia quelen

Abstract: The aim of this study was to evaluate the toxicity of tucumã oil nanocapsules from the Amazon region in silver catfish, Rhamdia quelen. Fish were exposed to water treated with different concentrations of tucumã nanocapsules, white, solubilized oil and surfactant vehicles. After three days of exposure, fish were euthanized and liver, gills and brain removed for analysis of the dichlorofluorescein, nitric oxide and PicoGreen ® assays. Plasma was collected for assay of hepatic transaminases. The nanocapsules had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Such anticancer activity may be related to the antioxidant activity of TPP oil, which is due to the presence of β-sitosterol, squalene (phytosterols), all-trans-β-carotene, and oleic acid [149]. A. vulgare oil nanocapsules were used to feed silver catfish Rhamdia quelen, and the results indicated that the oil could be an alternative non-toxic lipid source for fishes [195].…”
Section: Biological Effects Reported For Aptfosmentioning
confidence: 99%
See 2 more Smart Citations
“…Such anticancer activity may be related to the antioxidant activity of TPP oil, which is due to the presence of β-sitosterol, squalene (phytosterols), all-trans-β-carotene, and oleic acid [149]. A. vulgare oil nanocapsules were used to feed silver catfish Rhamdia quelen, and the results indicated that the oil could be an alternative non-toxic lipid source for fishes [195].…”
Section: Biological Effects Reported For Aptfosmentioning
confidence: 99%
“…In cosmetics, TAK oil has been employed as the lipid phase in nanocapsules [149,195] and biodiesel production via the alcohol route [212]. TPK oil was also successfully used to produce biodiesel using methanol and ethanol [44].…”
Section: Potential Applications Of Aptfosmentioning
confidence: 99%
See 1 more Smart Citation